In-situ Cu-doped MnCo-spinel coatings for solid oxide cell interconnects processed by electrophoretic deposition - Sabato, A. G.; Molin, S.; Javed, H.; Zanchi, E.; Boccaccini, Aldo R.; Smeacetto, F. (Ceramics International, 2019)
The Cu doping of the Mn–Co spinel is obtained “in-situ” by electrophoretic co-deposition of CuO and Mn1.5Co1.5O4 powders and subsequent two-step reactive sintering. Cu-doped Mn1.5Co1.5O4 coatings on Crofer22APU processed by electrophoretic co-deposition method are tested in terms of long term oxidation resistance and area specific resistance tests up to 3600 h. The introduction of Cu in the spinel lead to higher level of densification of coatings for all the considered aging periods at 800 °C and stabilizes the cubic phase of the Mn1.5Co1.5O4 spinel. Corrosion rate of the Cu-doped Mn1.5Co1.5O4 coated Crofer22APU is ∼10x lower than for the uncoated Crofer22APU. The stabilization of the cubic phase due to Cu doping, which reduces the extent of the tetragonal-cubic phase transition and limits possible thermal stresses due to mismatch of coefficients of thermal expansion or volume changes, is reviewed and discussed by means of electrical conductivity measurements together with diffraction patterns and elemental analyses. These novel electrophoretic co-deposited Cu-doped MnCo spinel coatings represent an innovative approach to obtain coatings with higher density and have future applications in the view of reaching lower rates of Cr evaporation form the steel.
CRIS-Team Scopus Importer:2019-06-28
Keywords: Coating; EPD; Solid oxide cell; Spinel